The role of nasopharyngeal examination and biopsy in the diagnosis of malignant diseases - Arslan,Necmi (2019)
Abstract Introduction: In direct proportion to the increasing rate of nasopharynx examinations applied, the early diagnosis and treatment of lesions in this region is possible. At times the clinical findings and the biopsy results are not consistent, so biopsies may have to be repeated. Objectives: The aim of this study was to evaluate the distribution of pathology test results obtained from cases of nasopharynx biopsy, to determine with which methods determination most often was made, and to investigate which kinds of cases required the biopsy to be repeated. Methods: The study included a total of 1074 patients (500 female, 574 male) who underwent nasopharyngeal biopsy in our clinic between June 2011 and June 2017. Data were obtained from patient records of age, gender, clinical findings, imaging findings if available and pathological diagnosis. The pathological diagnoses were separated into 3 main groups as chronic nasopharyngitis, benign cytology and malignant cytology. Results: The examinations resulted in 996 cases reported as chronic nasopharyngitis, 47 as benign cytology and 31 as malignant cytology. Of the 31 malignant lesions, diagnosis was made in 15 patients (48.4%) with a single biopsy, and in 16 patients (51.6%), as a result of the pathology report when 2 or more biopsies were taken. In the comparison of the benign and malignant lesions in respect of the need for repeated biopsies, the cases determined with malignancy were found to have a statistically significantly higher rate of repeated biopsy (p < 0.001). Conclusion: In comparison with cases of benign tumor, a statistically significantly greater number of repeated biopsies were required in cases diagnosed as malignant tumors to confirm the pathological diagnosis or when there was continued suspicion of malignancy. Therefore, when there is clinical suspicion, even if there are no findings of malignancy on the first biopsy, the biopsy should be repeated expeditiously.